A functionalized graphene aerogel for efficient water purification. Issue 1 (29th July 2020) - Cao, Chuan; Ren, Jing; Lv, Yong-Kang; Ren, Rui-Peng
Abstract : Water pollution has become a worldwide problem due to ever-increasing industrial wastewater. An ideal adsorbing material is able to remove oils, organic solvents and dyes from water efficiently, particularly with a high adsorption capacity and reusability. Herein, the authors report a novel strategy of synthesis of a three-dimensional functionalized graphene aerogel (FGA) with porous structures for effective water purification. The FGA is prepared by a facile one-step hydrothermal method, in which graphene oxide is reduced by ethylenediamine and modified by dodecyltrimethoxysilane to enhance hydrophobicity. When used as an adsorbing material, the FGA exhibits a high adsorption capacity (130–242 g/g for oils and organic solvents, 197–596 mg/g for dyes). Furthermore, the FGA also exhibits high reusability and durability by being reused for organic solvent–water separation for ten cycles without losing its hydrophobicity, which makes it a good candidate for industrial water treatment.